2021
DOI: 10.1186/s12941-021-00472-5
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and fungal growth in sputum cultures from 165 COVID-19 pneumonia patients requiring intubation: evidence for antimicrobial resistance development and analysis of risk factors

Abstract: Background Coronavirus SARS-CoV-2 causes COVID-19 illness which can progress to severe pneumonia. Empiric antibacterials are often employed though frequency of bacterial coinfection superinfection is debated and concerns raised about selection of bacterial antimicrobial resistance. We evaluated sputum bacterial and fungal growth from 165 intubated COVID-19 pneumonia patients. Objectives were to determine frequency of culture positivity, risk factors for and outcomes of positive cultures, and ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 85 publications
0
19
0
Order By: Relevance
“…To fight the inflammatory syndrome, many immunomodulant agents are used, such as corticosteroids, anti-interleukin-1 (IL-1), anti-interleukin-6 (IL-6), and inhibitors of the JAK-STAT pathway [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. The use of immune suppressive drugs, combined with the natural immune suppression caused by the virus, can lead to a surge of secondary bacterial and fungal infections [ 8 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…To fight the inflammatory syndrome, many immunomodulant agents are used, such as corticosteroids, anti-interleukin-1 (IL-1), anti-interleukin-6 (IL-6), and inhibitors of the JAK-STAT pathway [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. The use of immune suppressive drugs, combined with the natural immune suppression caused by the virus, can lead to a surge of secondary bacterial and fungal infections [ 8 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the contrary, Tang (2021) found that only about 6% of bacterial infections were caused by a single organism (30). Results from sputum cultures showed a mixed infection type in 8.7% of 165 patients in one study (Liu HH et al, 2021). (19).…”
Section: Discussionmentioning
confidence: 93%
“…This finding may be explained by the fact that patients in this age range are more likely to have other predisposing diseases, such as diabetes mellitus, hypertension, liver dysfunction, or kidney failure. The research was conducted in the United States (Liu HH et al, 2021) (19). People between the ages of 56 and 80 had the highest infection rate (43%).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary vascular dysfunctions described in COVID-19 ARDS are not captured by the CTSS and RALE score [ 29 , 30 , 31 , 32 , 33 , 34 ]. Aside from thrombo-embolic complications, mortality may be also driven by other factors, such as bacterial and fungal infections complications [ 35 , 36 ] and ICU-acquired weakness. The initial ventilator management was also shown to moderate the prognostic value of other predictive parameters [ 37 ].…”
Section: Discussionmentioning
confidence: 99%